Hubungan Manajemen Konflik Dan Stres Kerja Terhadap Kinerja Melalui Peran Motivasi Sebagai Variabel Intervening - Dewi Virgiaswari; Arisyahidin Arisyahidin (Universitas Islam Kadiri, 2022)
Efforts to improve employee performance include paying attention to work stress, conflict and motivation within the organization. The purpose of this study was to identify and analyze the impact of conflict, stress and motivation on employee performance. This study is a quantitative study using primary data, which aims to provide a description of the characteristics of the data that was tested in the study. The population in this study were all Blitar Regency General Apparatus with a total of 37 people. The sampling technique used is the saturated sample. In this study, the sample used was 37 Apparatus of the General Section of Blitar Regency. This research uses data analysis method using SPSS software. The results of the research carried out showed that conflict management had an effect on the work motivation of the general apparatus of the Regional Secretariat of Blitar Regency. the performance of the general apparatus of Blitar district, work motivation has an effect on performance, conflict management has an effect on performance through work motivation in the general part of the Blitar district secretariat, and work stress affects performance through work motivation in the general part of the Blitar district secretariat.